Does Investment Reduce Unemployment? An Empirical Study of FDI and DDI Impacts in Bandung Regency - Simamora, Daniel (Quantitative Economics and Management Studies, 2025)
This study investigates the comparative influence of Foreign Direct Investment (FDI) and Domestic Direct Investment (DDI) on the Open Unemployment Rate (OUR) in Bandung Regency. This study utilizes annual time-series data covering the period from 2007 to 2024 for the OUR variable, as well as deflated FDI and DDI realization values. The methodology adopted is a quantitative approach with an Ordinary Least Squares (OLS) regression model specified in a log-log form to analyze the elasticity relationship between variables. The model estimation results show that DDI has a negative and statistically significant effect on the OUR, with an elasticity coefficient of -0.285, implying that a 1% increase in real DDI will decrease the OUR by 0.285%. Conversely, FDI was found to have no statistically significant effect on the OUR at a 5% significance level. The main finding of this research is the clear difference in effectiveness between the two capital sources in local labor absorption. DDI proves to be a strong determinant in reducing unemployment, whereas FDI, despite its volume, shows no significant statistical impact. This finding highlights that domestic investment plays a more crucial and direct role in addressing unemployment issues at the regency level, such as in Bandung Regency. Keywords: Foreign Direct Investment, Domestic Direct Investment, Open Unemployment Rate, OLS Regression